1997
DOI: 10.1182/blood.v90.1.331.331_331_339
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Oligodeoxyribonucleotides Suppress Hematologic Cell Growth Through Stepwise Release of Deoxyribonucleotides

Abstract: Antisense oligodeoxyribonucleotides (ODNs) are now being extensively investigated in an attempt to achieve cell growth suppression through specific targeting of genes related to cell proliferation, despite increasing evidence of non-antisense cytotoxic effects. In the context of anti-BCR/ABL antisense strategies in chronic myeloid leukemia, we have re-examined the antiproliferative effect of phosphodiester and phosphorothioate ODNs on the leukemic cell line BV173 and on CD34+ bone marrow cells in liquid cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…[1] Chemical modifications to the phosphodiester backbone are commonly incorporated into synthetic oligonucleotides to increase stability and safety in vivo against endo-and exonucleases as well as improve efficacy through increased cellular uptake and binding properties. [1,8,9] While the synthesis process of oligonucleotides is well controlled, several factors can alter the end product. Quality of starting materials can impact the purity of products while random insertion/deletions can result in improper sequence generation.…”
mentioning
confidence: 99%
“…[1] Chemical modifications to the phosphodiester backbone are commonly incorporated into synthetic oligonucleotides to increase stability and safety in vivo against endo-and exonucleases as well as improve efficacy through increased cellular uptake and binding properties. [1,8,9] While the synthesis process of oligonucleotides is well controlled, several factors can alter the end product. Quality of starting materials can impact the purity of products while random insertion/deletions can result in improper sequence generation.…”
mentioning
confidence: 99%
“…Although the 36-nucleotide abl-directed circle was inactive, the 34-nucleotide bcr-directed circle had activity. At 13 ,uM, the bcr circle reduced the saturating cell number by 68% (note the log scale) (Fig. 2).…”
Section: Resultsmentioning
confidence: 92%
“…Many studies used phosphorothioates that can have nonspecific effects. Some investigators claim the mechanism is other than an antisense one, i.e., a sequence-dependent mechanism unrelated to the bcr-abl sequence (12,13). Others have found no effect on the bcr-abl protein level (14) or direct inhibition of the bcr-abl-associated protein-tyrosine kinase activity (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…389 Sequence dependent but non-antisense effects can probably be caused by the interaction of specific nucleotide sequences such as TAT and GCC with proteins. 390 Vaerman et al 391 demonstrated a novel non-antisense mechanism of ASODNs. They showed that the antiproliferative effect of ASODNs is correlated with the absence of a cytosine residue at the 3Ј position.…”
Section: In Vitro Purgingmentioning
confidence: 99%